A meta-analysis of tradeoffs between plant tolerance and resistance to herbivores: combining the evidence from ecological and agricultural studies - Leimu, R; Koricheva, J (2012)
Resistance and tolerance represent two general strategies of plant defence against herbivores. Since resources available for allocation to defence are limited and resistance and tolerance are likely to serve the same functions for plants, the occurrence of trade offs between these two strategies has been assumed. We review the empirical evidence for tolerance-resistance tradeoffs by means of meta-analysis of genetic correlations between resistance and tolerance obtained from 31 ecological and agricultural studies published during 1980-2003 and conducted on 17 different plant species. The sign of the relationship between tolerance and resistance differed depending on the type of plants examined. Tolerance and resistance tended to be positively correlated in crops and negatively correlated in wild plants, but the mean correlation coefficients in both plant types were not significantly different from zero. The magnitude of correlations was affected neither by the tolerance measure (reduction in growth or in fitness in damaged plants) nor by the resistance measure used (inverse of damage, antibiosis, antixenosis, or specific resistance trait). In wild plants correlations between resistance and tolerance were significantly negative (r=-0.069) only in studies where resistance was assessed as a specific chemical or mechanical resistance trait, but this correlation is based only on two studies. No difference in the mean resistance-tolerance correlations was found between studies conducted in the field and in the greenhouse; in both cases mean correlations tended to be positive. The results of our analysis indicate that conditions under which a negative association between resistance and tolerance occurs and, thus, the evolution of multiple defensive strategies in plants is constrained, are much more restrictive than previously assumed. However, the currently available studies are still scarce and taxonomically skewed to allow a thorough analysis of sources of variation in resistance-tolerance relationship. Specifically, we need more studies examining the relationship between specific resistance and tolerance traits, studies on perennial plants and under different environmental conditions. Copyright © Oikos 2006.